REVITALISASI PENDIDIKAN KEAGAMAAN ISLAM ERA DIGITAL 4.0 - Indra, Hasbi (Tawazun: Jurnal Pendidikan Islam, 2019)
Islamic religious of schools that Qur'anic Education, Diniyah and Islamic Boarding School, have Regulation Goverment No. 20/2003, those of a place urgent for development of nations in the future. The Nasional of Education Systems have varians of national education and foundation education have bring a quality its are equity with general Education. The quality of national schools system have under position in Asian State that Singapura, Thailand, Malaysia and Vietnam. This time and in the future Islamic religious school are face of competation with schools in regional as well as international. This era a degree amongts on Asian Nations in freedom trade in MEA. This religious education cannot be avoided and the alumni must prepare themselves with science and technology as well as other competencies or skills. There is already an instrument in this education but to respond to the challenges that need revitalization in its curriculum and this education is managed with total quality management. Abstrak Pendidikan keagamaan Islam seperti Taman Pendidikan Al-Quran, Diniyah dan Pesantren telah dipayungi oleh UU No. 20/2003 dan menjadi salah satu pilar penting dalam pengembangan pendidikan nasional ke depan. Pendidikan ini telah menjadi bagian dari sistem pendidikan nasional yang kualitasnya diarahkan setara dengan pendidikan nasional pada umumnya dan bahkan pada tingkat regional maupun internasional. Kualitas pendidikan nasional yang di dalamnya ada pendidikan ini masih berada di bawah negara-negara Asia seperti Singapura, Thailand, Malaysia dan Vietnam. Saat ini dan mendatang produk pendidikan berada di tengah kompetisi perdagangan antar negara di tingkat regional maupun internasional. Di masa ini telah menghadapi perdagangan bebas antar negara Asia yang disebut dengan MEA. Hal ini tidak bisa dihindari oleh pendidikan keagamaan ini dan alumninya harus menyiapkan dirinya dengan ilmu dan teknologi serta kompetensi atau keterampilan lainnya. Telah ada di pendidikan ini instrumennya namun untuk merespons tantangan yang ada diperlukan revitalisasi di kurikulumnya dan pendidikan ini dikelola dengan total quality management.